Strategi Brand Awareness Yoona Women dalam Mengoptimalisasikan Program Komunitas Wellness Yoona Squad Leader - Zerlynda Ali; Hudi Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the optimization of the Yoona Squad Leader wellness community program in strengthening the brand awareness of Yoona Women. The increasing awareness of feminine hygiene and the growing concern regarding the safety of menstrual products serve as the foundation of this research, considering that more than half of Indonesian women report irritation and discomfort related to conventional sanitary pad use (Manoppo, 2022; Putinah et al., 2020). In addition, laboratory findings by the Indonesian Consumers Foundation (YLKI, 2015) revealed traces of chlorine and dioxin in many commercial sanitary pads, indicating potential reproductive health risks. The study employed a descriptive qualitative approach through observation, interviews, and active participation in the marketing division of PT Yoona Digital Indonesia during August–December 2025. The findings show that the Yoona Squad Leader program effectively strengthens all stages of the 5A Customer Path—Awareness, Appeal, Ask, Act, and Advocate—as conceptualized in Marketing 5.0: Technology for Humanity (Kotler, Kartajaya, & Setiawan, 2021). Community-based engagement drives emotional bonding, advocacy behavior, and value-based loyalty through empathy-driven communication. This program successfully empowers women to become advocates for menstrual health awareness while reinforcing brand credibility and consumer trust. The study highlights the strategic importance of community-based marketing as a sustainable approach to building human-centered loyalty and enhancing brand equity in the digital wellness industry.